PENGANTAR POLITIK ISLAM DAN ISLAM POLITIK - Istadiyantha Istadiyantha (CMES (Center of Middle Eastern Studies), 2014)
Politic has been defined simply by Harold Laswell as who gets what, when, how?Many people say that politic is synonymous with power. The "power" is the ability of agroup to influence other groups according to the subject wishes. Furthermore, thepolitical experts see the power as a political core and also assume that politic is all amatter of fight and maintain activities power. It has a purpose related to the interests of the entire community. On the other hand mentioned that politic is the process offormation and distribution of a power in society such as decision-making process,particularly in countries. This understanding is the incorporation effort between manydifferent definitions of the political nature which is known in political science. Politic is the art and science to gain power constitutionally and unconstitutionally. Principally political Islam is to actualize Islamic law as the supreme source of lawin the national legal order. All laws and regulations applicable in a country should refer to the highest legal source Shari'a. If there is any conflict with the shari‟a, then it is automatically canceled regulations. Politics that do not have a mission like this can not be classified as political Islam.